Experiential Learning dalam Pembelajaran Agama Anak Usia Dini Berbasis Sekolah Alam di TKIT Nurul Islam Yogyakarta - Rohinah, Rohinah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
The research analyzes the relevance of experiential learning in religious learning in early childhood Islamic education institutions based on the natural school of Nurul Islam Yogyakarta. Experiential learning in religious learning is believed to help learners especially in early childhood to increase tadabbur nature and more closer to the real experience in life. The implementation model of experiential learning can be an alterative for us educators to introduce more concrete diverse creations of Allah SWT. Experiential learning can utilize locations such as rice fields, plantations, museums, zoos, school gardens, school grounds, and industrial premises. In addition, activities that can be done in the form of outbound, field trip, and tracking. Therefore, the relevance of experiential learning in the learning of religion is able to instill religious values in the students with a concrete.R